2017
DOI: 10.5551/jat.34900
|View full text |Cite
|
Sign up to set email alerts
|

CHADS<sub>2</sub> and CHA<sub>2</sub>DS<sub>2</sub>-VASc Scores Predict the Risk of Ischemic Stroke Outcome in Patients with Interatrial Block without Atrial Fibrillation

Abstract: Aim: To evaluate the role of CHADS2 and CHA2DS2-VASc scores in predicting the risk of ischemic stroke or transient ischemic attack (TIA) outcomes in patients with interatrial block (IAB) without a history of atrial fibrillation (AF).Methods: A retrospective study was conducted, including 1,046 non-anticoagulated inpatients (612 males, 434 females; mean age: 63 ± 10 years) with IAB and without AF. IAB was defined as P-wave duration > 120 ms using a 12-lead electrocardiogram. CHADS2 and CHA2DS2-VASc scores were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 47 publications
4
26
0
4
Order By: Relevance
“…1) A recent review of the prevalence of IAB described this condition as being an under-appreciated clinical pandemic, particularly in the aging population. 2) IAB can be associated with a multitude of medical conditions, including atrial fibrillation (AF), [3][4][5][6][7][8] left atrial electromechanical dysfunction, 1,9) thromboembolic ischemic stroke, [10][11][12][13] and increased cardiovascular and all-cause mortalities. 14) Therefore, it is crucial that patients who are at an increased risk for developing IAB are identified.…”
mentioning
confidence: 99%
“…1) A recent review of the prevalence of IAB described this condition as being an under-appreciated clinical pandemic, particularly in the aging population. 2) IAB can be associated with a multitude of medical conditions, including atrial fibrillation (AF), [3][4][5][6][7][8] left atrial electromechanical dysfunction, 1,9) thromboembolic ischemic stroke, [10][11][12][13] and increased cardiovascular and all-cause mortalities. 14) Therefore, it is crucial that patients who are at an increased risk for developing IAB are identified.…”
mentioning
confidence: 99%
“…Wu et al. () also found this association between IAB and stroke in patients with high CHA 2 DS 2 ‐V score. Finally, Martínez‐Sellés, Massó‐van Roessel, et al., found that centenarians with IAB presented a higher prevalence of cognitive impairment and previous stroke than centenarians with normal P wave.…”
Section: Advanced Interatrial Block As a Risk Marker Of Af And Strokementioning
confidence: 65%
“…In 2012, a consensus paper defined the current ECG diagnostic criteria: partial IAB (P‐wave duration ≥120 ms) and advanced IAB (P‐wave duration ≥120 ms plus biphasic [plus/minus] morphology in inferior leads II, III, and aVF). The interest in this topic has increased in recent years, and a large number of studies recently have been published regarding the prevalence of IAB and its associations with the risk of AF, ischemic stroke, and cognitive decline . However, most studies have been performed retrospectively in the general population, where, even in the presence of IAB, the incidence of AF and stroke is low.…”
Section: Introductionmentioning
confidence: 99%
“…The interest in this topic has increased in recent years, and a large number of studies recently have been published regarding the prevalence of IAB and its associations with the risk of AF, ischemic stroke, and cognitive decline. [7][8][9][10][11][12][13][14][15] However, most studies have been performed retrospectively in the general population, where, even in the presence of IAB, the incidence of AF and stroke is low. Little information exists about the prognosis of elderly patients with heart disease and IAB.…”
Section: Introductionmentioning
confidence: 99%